The daily Life of children infected by HIV in the process of becoming adolescent: compromise and pos sibilities to the care for themselves - Paula, Cristiane C.; Cabral, Ivone E.; Souza, Ívis Emilia O. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: children with vertical transmission HIV/aids pass from childhood to adolescence and little is known about how they care about themselves. Objective: understand the possibilities of the care for oneself in the daily life of adolescents with aids. Methods: phenomenological interview was developed with 11 non-institutionalized 12-14 year-old-boys and girls with disclosed diagnosis from Brazilian teaching hospitals. The project was approved by the Ethics Review Committees. Heiddeger’s hermeneutic analyzes was applied. Results: since that “thing in the blood” was found they have to take medication everyday, many times and ever. When they discovered about the “virus”, they understood that they had to take care of their health to continue alive, to go alone to consultation, to take medical exams and have control about their treatment. Due to adolescence they have to change doctors. They have to take medication in the right way to be healthy, to have biological immunity, and avoid diseases and “worst things”. They get tired. The pills’ size/flavor is bad and interfere in their daily live. Some take medication alone, but following the treatment is hard, so they need help. Some never stopped the treatment, however, others did that due to medical orientation or because they did not accept the “problem”. They know that nutrition and physical activities help the treatment. Conclusion: aids determined a special need in their health: the medication technology dependency. The facticity involved them in a web care by professionals and relatives. During childhood, they needed family care integrally; and, in the transition from childhood to adolescence, they have to take care of themselves acquiring responsibilities with-themselves and being helped by relatives. Thus, children were revealed in the movement from being- cared-for to being-cared-with.